The differential impact of a 6-versus 12-month pharmacist-led interprofessional medication adherence program on medication adherence in patients with diabetic kidney disease: the randomized PANDIA-IRIS study - Bandiera, Carole; Dotta-Celio, Jennifer; Locatelli, Isabella; Nobre, Dina; Wuerzner, Grégoire; Pruijm, Menno; Lamine, Faiza; Burnier, Michel; Zanchi, Anne; Schneider, Marie Paule (Frontiers in Pharmacology, 2024)
Background: For every 100 patients with diabetes, 40 will develop diabetic kidney disease (DKD) over time. This diabetes complication may be partly due to poor adherence to their prescribed medications. In this study, we aimed to evaluate the differential impact of a 6- versus 12-month pharmacist-led interprofessional medication adherence program (IMAP) on the components of adherence (i.e., implementation and discontinuation) in patients with DKD, during and after the intervention. Methods: All included patients benefited from the IMAP, which consists in face-to-face regular motivational interviews between the patient and the pharmacist based on the adherence feedback from electronic monitors (EMs), in which the prescribed treatments were delivered. Adherence reports were available to prescribers during the intervention period. Patients were randomized 1:1 into two parallel arms: a 12-month IMAP intervention in group A versus a 6-month intervention in group B. Adherence was monitored continuously for 24 months post-inclusion during the consecutive intervention and follow-up phases. In the follow-up phase post-intervention, EM data were blinded. Blood pressure was measured by the pharmacist at each visit. The repeated measures of daily patient medication intake outcomes (1/0) to antidiabetics, antihypertensive drugs, and statins were modeled longitudinally using the generalized estimated equation in both groups and in both the intervention and the follow-up phases. Results: EM data of 72 patients were analyzed (34 in group A and 38 in group B). Patient implementation to antidiabetics and antihypertensive drugs increased during the IMAP intervention phase and decreased progressively during the follow-up period. At 12 months, implementation to antidiabetics was statistically higher in group A versus group B (93.8% versus 86.8%; Δ 7.0%, 95% CI: 5.7%; 8.3%); implementation to antihypertensive drugs was also higher in group A versus B (97.9% versus 92.1%; Δ 5.8%, 95% CI: 4.8%; 6.7%). At 24 months, implementation to antidiabetics and antihypertensive drugs remained higher in group A versus B (for antidiabetics: 88.6% versus 85.6%; Δ 3.0%, 95% CI: 1.7%; 4.4% and for antihypertensive drugs: 94.4% versus 85.9%; Δ 8.5%, 95% CI: 6.6%; 10.7%). No difference in pharmacy-based blood pressure was observed between groups. Implementation to statins was comparable at each time point between groups. Three patients discontinued at least one treatment; they were all in group B. In total, 46% (16/35) of patients in the 12-month intervention versus 37% (14/38) of patients in the 6-month intervention left the study during the intervention phase, mainly due to personal reasons. Conclusion: The IMAP improves adherence to chronic medications in patients with DKD. The longer the patients benefit from the intervention, the more the implementation increases over time, and the more the effect lasts after the end of the intervention. These data suggest that a 12-month rather than a 6-month program should be provided as a standard of care to support medication adherence in this population. The impact on clinical outcomes needs to be demonstrated. Clinical Trial Registration:Clinicaltrials.gov, identifier NCT04190251_PANDIA IRIS.